Direito fundamental a moradia dos imigrantes no Brasil: implementação de políticas públicas de moradia - Silva, Silvana de Fátima Machado da (2020)
This dissertation is part of the Social Relations and Dimensions of Power Research Line. The general objective of this work is to conduct a social and legal reflection aimed at identifying ways to guarantee immigrants the right to decent housing, effectively applying fundamental social rights. The first chapter provides a historical overview of migratory movements, wars, and conflicts that drive waves of migration around the world. This is followed by a historical approach to immigration in Brazil, a reality that has given rise to the need for migratory policies to implement reception measures. It also discusses migratory processes and the difficulties faced by the immigrant population in the process of social inclusion. The second chapter examines the application of fundamental social rights, focusing on the right to housing as a fundamental human right applicable to immigrants, which must be effectively recognized and included in urban planning and housing policies of the States. The third chapter of this dissertation examines the public policies at the Federal, State, and Municipal levels regarding the right to housing of foreigners. Over the years, Brazil has made international commitments to guarantee the right to decent housing, and their implementation requires efficient housing policies, as well as effective government policies that guarantee access to housing for all citizens, although in practice this does not happen efficiently. The investigation method was dialectical, which allowed for debate and argumentation about history and ideas themselves, seeking to understand the reality in constant transformation; the procedural method was historical, to verify how past events influence society. Finally, to carry out the investigation process, documentary and bibliographic techniques were used, supported by international normative instruments, domestic legislation, bibliographic sources such as books, publications, periodicals, and similar materials. The conclusion was that it is essential to build a more altruistic and humanitarian society, capable of recognizing itself in others, and thus, when we achieve this ideal, walls and borders will be mere physical marks, and everyone, regardless of class or origin, will be able to live as dignified human beings.